Erosion: Prevention and Useful Applications 1979
DOI: 10.1520/stp35803s
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Brittle Target Fracture from a Subsonic Water Drop Impact

Abstract: The erosive damage of an infrared transparent material by a subsonic water drop impact has been numerically simulated. The important early-time pressure loading characteristics from a water drop impact are discussed, and the predicted target damage (in terms of fracture patterns) is presented for variations in material flaw size, material gain size, and impact velocity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
1

Year Published

1985
1985
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 4 publications
0
7
0
1
Order By: Relevance
“…This picture of jetting is contrary to w hat has often been described in the drop-impact literature (even by the present authors). However, careful study of our photographic evidence and of plots of computer simulations (Rosenblatt et al 1979) support the view th a t the jetting motion is initially towards the target surface rather than tangential to it. The relief waves moving into the drop soon bring the high-pressure phase of the process to an end, with the additional development, which can be observed in the experiments of Camus (1971), th a t the crossing of the relief waves produce sufficient tensile stresses to initiate cavitation of the liquid.…”
mentioning
confidence: 68%
“…This picture of jetting is contrary to w hat has often been described in the drop-impact literature (even by the present authors). However, careful study of our photographic evidence and of plots of computer simulations (Rosenblatt et al 1979) support the view th a t the jetting motion is initially towards the target surface rather than tangential to it. The relief waves moving into the drop soon bring the high-pressure phase of the process to an end, with the additional development, which can be observed in the experiments of Camus (1971), th a t the crossing of the relief waves produce sufficient tensile stresses to initiate cavitation of the liquid.…”
mentioning
confidence: 68%
“…where the subscript s refers to the solid body variables. It is then concluded in several studies [62][63][64][65] that the impact pressure has spatial and temporal distribution in the impact zone, as well as a maximum peak value that occurs at a critical contact radius (r c ). The maximum peak value was seen to be more important than the full pressure distribution and many equations to quantify the maximum peak pressure were provided, such as Heymann's approximation [63]:…”
Section: Water Hammer Pressurementioning
confidence: 99%
“…The full temporal and spatial distribution of the impact pressure was provided by many numerical works [65][66][67][68][69], where some such as Rosenblatt et al [65] confirmed Heymann's approximation of the maximum peak pressure. Once the impact pressure is obtained, it is usually used as a boundary loading condition acting on the solid target.…”
Section: Water Hammer Pressurementioning
confidence: 99%
See 1 more Smart Citation
“…Une approche monodimensionnelle du choc élastique du microjet contre la paroi opposée permet de donner l'ordre de grandeur de l'amplitude de l'onde de choc, selon la nature de la paroi -dans le fluide : [5]. L'échelle de temps caractéristi-que de cette onde est liée à la taille du microjet :…”
Section: With the Aim Ofgainingunclassified